Intra-Aortic Balloon Pump May Grant No Benefit to Improve the Mortality of Patients With Acute Myocardial Infarction in Short and Long Term. Issue 19 (May 2015) - Su, Dan; Yan, Bin; Guo, Litao; Peng, Liyuan; Wang, Xue; Zeng, Lingfang; Ong, HeanYee; Wang, Gang; Lymperopoulos, Anastasios
<x xml:space="preserve">Abstract</x> Abstract Intra-aortic balloon pump (IABP) has been extensively used in clinical practice as a circulatory-assist device. However, current literature demonstrated significantly varied indications for IABP application and prognosis. The objective of the study was to assess the potential benefits or risks of IABP treatment for acute myocardial infarction (AMI) complicated with or without cardiogenic shock. MEDLINE and EMBASE database were systematically searched until November 2014, using the terms as follows: IABP, IABC (intra-aortic balloon counterpulsation), AMI, heart infarction, coronary artery disease, ischemic heart disease, and acute coronary syndrome. Only randomized controlled trials (RCTs) that compared the use of IABP or non-IABP support in AMI with or without cardiogenic shock were included. Two researchers performed data extraction independently, and at the mean time, the risk of bias among those RCTs was also assessed. Of 3026 citations, 17 studies (n = 3226) met the inclusion criteria. There is no significant difference between IABP group and control group on the short-term mortality (relative risk [RR], 0.90; 95% confidence interval [CI], 0.77–1.06; P = 0.214) and long-term mortality (RR, 0.91; 95% CI, 0.79–1.04; P = 0.155) in AMI patients with or without cardiogenic shock. These results were consistent when the analysis was performed on studies that only included patients with cardiogenic shock, both on short-term mortality (RR, 0.91; 95% CI, 0.77–1.08; P = 0.293) and long-term mortality (RR, 0.95; 95% CI, 0.83–1.10; P = 0.492). Similar result was also observed in AMI patients without cardiogenic shock. Furthermore, the risks of hemorrhage (RR, 1.49; 95% CI, 1.09–2.04; P = 0.013) and recurrent ischemia (RR 0.54, 95% CI 0.37 to 0.79; P = 0.002) were significantly higher in IABP group compared with control group. We did not observe substantial benefit from IABP application in reducing the short- and long-term mortality, while it might promote the risks of hemorrhage and recurrent ischemia. Therefore, IABP may be not an optimal therapy in AMI with or without cardiogenic shock until more elaborate classification is used for selecting appropriate patients.